Aplicação do procedimento de decomposição comportamental para a descrição de competências no contexto público federal - RAMOS, Camila Carvalho (Universidade Federal do Pará, 2018)
The Competency Management model was introduced in Brazil through Decree 5,707 / 2006 to guide the development of personnel in the Federal Public Administration. Although many organizations seek to implement this new management model, little attention has been given to the description of ompetencies. According to previous researches, teaching objectives or, in this study, competence, need to specify the concrete behavior of a professional who should be learned or improved from the training activities. The objective and exact specification of these competencies is a crucial first step in the whole process of management. The aim of this study was to apply the behavioral decomposition procedure to improve the description of competencies a federal public institution. To do so, they were prepared and analyzed five problematic conditions of the descriptions of competencies which could hinder its operation. The study was conducted in a federal public institution was divided into the following phases: 1) Competency Mapping, 2) Categorization; 3) Analysis of the descriptions of competencies and behavioral decomposition. As a result of mapping it has identified 191 competencies. The decomposition results showed that 93.20% of skill descriptions presented at least one of the five problematic conditions. In addition, when analyzing and decomposing mapped competencies have been identified behavioral 1,168 units. The results confirm the suitability of the decomposition procedure to improve the description of competencies. The categorization of failures formulation, developed in the educational context, proved useful to the organizational context. Subsequent studies should explore the possible impact of the procedure here about the effectiveness of subsequent stages of management by competencies such as setting priorities for training activities for the institution to achieve its strategic objectives.